New perspectives on young children's moral education developing character through a virtue ethics approach - Eaude, Tony (London Bloomsbury Academic, 2016)
"New Perspectives on Young Children's Moral Education explores how to approach young children's moral education in a world of uncertainty and change" -- Provided by publisher.
Introduction -- Part I. The Context of Young Children's Moral Education -- 1. The Landscape of Moral Education -- 2. The Basis of Ethics -- 3. The Changing Social and Cultural Context -- 4. The Educational Context -- Part II: The Roots of Moral Development -- 5. How Young Children Learn -- 6. Culture, Identity and Motivation -- 7. Learning to Live a Good Life -- Part III: Routes into Moral Education -- 8. Inclusive Learning Environments -- 9. Encouraging Empathy and Thoughtfulness -- 10. Moving Beyond Separate Programmes -- 11. Gathering the Threads -- Bibliography -- Index.
Includes bibliographical references (pages 189-196) and index.
Keywords: Moral education (Early childhood).; Moral education (Elementary).; Ethics -- Study and teaching (Early childhood).; Ethics -- Study and teaching (Elementary).